Representasi Pembawa Acara Program Talk Show di Televisi Indonesia - Rahmat Edi Irawan (Humaniora, 2013)
Presentation of talk show host program has been known to be intelligent, smart, and is able to direct the conversation in the program well. The presentation is in line with the view of talk show programs packed seriously as a journalistic genre program with emphasis on the truth of the facts or information conveyed. However, in recent years there are different representations associated with the talk show host of the program. The representation shows that a talk show host is not such intelligent and smart, and is not able to direct the conversation in the program properly. The existence of this representation is consistent with the theory of social construction assuming that mass media play a major role in shaping the social reality in the society. As of this writing, the audience receives social reality as a representation. Like the previous presentation, as the television has broadcasted for a long time, people feel that the reality is normative and ideal conditions for them. Public realize that the social reality was only the reconstruction of the television when TV presents a representation of another social reality. Nevertheless, whatever the social reality that is deliberately made or reconstructed by the media, including television, in fact everything is a reality that is deliberately created just for the sake of the manager or owner of the television station.